Tax Allocation in Perspective. - Winborne, Marilyn G.; Kleespie, Dee L. (The Accounting Review, 1966)
This article brings into perspective the three major questions involved in allocation of income tax within the financial statements of non-regulated businesses in the U.S. in 1966. The first is the nature of Federal income taxes. The second question is derived from the first, the desirability of allocation. The third question is about what to do with the balance-sheet element resulting from allocation procedures. The author concludes that to match income tax with the related items, the expense and the amount payable will frequently differ.